Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai Melalui Kepuasan Kerja pada Rumah Tahanan Negara Klas II B Padang - Gaury Febriani; Vicky Brama Kumbara; M. Afuan; Zelfi Yeni; Hilda Mary (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This research aims to find out how much influence work motivation and work discipline have on employee performance through job satisfaction at the Class II B State Detention Center in Padang. Documentation methods and types of primary data.. Research results obtained based on partial tests (T tests) obtained: There is a significant positive influence of motivation on job satisfaction at the Kles II B Padang State Detention Center. There is a significant positive influence of Work Discipline on Job Satisfaction at the Kles II B Padang State Detention Center. The largest or dominant value is 0.906. There is an insignificant positive effect of motivation on employee performance at the Kles II B Padang State Detention Center. The largest or dominant value is 0.899. There is an insignificant positive influence of Work Discipline on Employee Performance at the Kles II B Padang State Detention Center. The largest or dominant value is 0.906. There is a significant positive influence of Job Satisfaction on Employee Performance at the Kles II B Padang State Detention Center. The largest or dominant value is 0.859. Job Satisfaction is able to mediate Motivation on Employee Performance at the Kles II B Padang State Detention Center. The largest or dominant value is 0.899 and the smallest value is 0.822. Job Satisfaction is able to mediate Work Discipline on Employee Performance at the Kles II B Padang State Detention Center. The largest or dominant value is 0.906.